Dividing by demanding: object division through market procedures - Claus-Jochen Haake (Bielefeld University, Institute of Mathematical Economics (IMW), 2004)
We discuss a model, in which two agents may distribute finitely many objects among themselves. The conflict is resolved by means of a market procedure. Depending on the specifications, this procedure serves to implement bargaining solutions such as the discrete Raiffa solution, the Kalai-Smorodinsky solution and the Perles-Maschler solution. The latter is axiomatized using the superadditivity axiom, which in the present context is readily interpreted as resolving a specific source of conflict potential.
urn:nbn:de:hbz:361-6050
Keywords: C78; C62; D51; D63; 330; Object Division; Market Procedure; Perles-Maschler Solution; Verhandlungstheorie; Allgemeines Gleichgewicht